Pengaruh Bahan Kemasan terhadap Kualitas dan Daya Simpan Buah Jambu Biji Merah (Psidium guajava L.) - Ummu Kalsum; Dewi Sukma; Slamet Susanto (Universitas Gunadarma, 2017)
Guava (Psidium guajava L.) was horticulture commodity, that has easy damaged and fleshy. Lacking of storage facility, limitation of transportation access and risk of high weight loss resulted in castaway fruit and it has shortened shelf life. Packing could help to prevent or less damages. The aims of this research was to evaluate the effect of packing materials on quality and shelf life of guava. This research has been conducted at Postharvest Laboratory, Agronomy and Horticulture Department of Bogor Agricultural University in March 2013. The experiment was arranged in completely randomized design with one factor, that is materials packing (without packing (control), polypropylene (PP) plastic and wrapping). Data analysis used analysis of variance (anova) at level α = 5%, then Duncan Multiple Range Test (DMRT) at level α = 5%. The result showed that using of packing materials increased shelf life length of guava than control treatment. Packing with PP plastic could be recommended because it has best fruit quality, i.e. shelf life until 7 days after treatment and the fruits still qualified to consume.